Examining the Evolutionary Relationships Amongst Three Species of West African Freshwater Crabs Liberonautes (Brachyura: Potamonautidae) Using MTDNA Sequence Data. Issue 5 (1st September 2016) - Daniels, Savel R.; McLeod, Curtiss; Carveth, Corissa; Mexim, Konan K.; Cumberlidge, Neil
Abstract: Evolutionary relationships amongst three species of freshwater crabs, Liberonautes latidactylus (De Man, 1903 ), L. nimba Cumberlidge, 1999, and L. rubigimanus Cumberlidge and Sachs, 1989, were examined using DNA sequence data of the mitochondrial cytochrome oxidase subunit I (COI) locus. The latter three species are listed in the IUCN Red List for 2008 as least concerned, vulnerable, and endangered, respectively. Specimens of the three species were collected in Liberia and neighbouring Guinea, West Africa. Phylogenetic results derived from maximum parsimony, maximum likelihood, and Bayesian inference revealed the monophyly of all three species. Moderate genetic variation was observed within L. latidactylus . Within the narrow endemic, montane species, L. nimba shallow divergence was observed, whereas marked genetic divergence was observed within L. rubigimanus . Three statistically well-supported clades were observed within the latter taxon, two of these clades were sympatric at Simandou, Liberia (clades A and B), and characterised by a 10% uncorrected sequence divergence for the COI locus, whereas the divergence between the latter two clades and the larger L. rubigimanus clade was 8% . Haplotype networks corroborate the absence of maternal gene flow amongst the three L. rubigimanus clades suggesting possible reproductive isolation and the presence of two novel species. Our results suggest that Liberonautes harbours undescribed, narrowly distributed species. The results are discussed in a conservation framework for the three Liberonautes species.